Electron‐Deficient Sites for Improving V2+/V3+ Redox Kinetics in Vanadium Redox Flow Batteries. (23rd February 2022) - Huang, Rongjiao; Liu, Suqin; He, Zhen; Zhu, Weiwei; Ye, Guanying; Su, Yuke; Deng, Weiwen; Wang, Jue
Abstract: Fundamental kinetics of the V 2+ /V 3+ of vanadium redox flow battery (VRFB) are still not well understood despite tremendous efforts in improving the sluggish kinetics of V 2+ /V 3+ . This article first reveals the rate‐determining step in the electrochemical oxidation of V 2+ to V 3+ by exploring the reaction kinetics. Thereafter, TiB2 with abundant electron‐deficient sites, which possesses a strong electron‐accepting ability, is demonstrated to improve the rate‐determining step of V 2+ /V 3+ by enhancing the electron transfer from V 2+ to the electrode. The mechanism of TiB2 for boosting V 2+ /V 3+ kinetics is also unraveled by analyzing the reaction order. VRFB with the electron‐deficient TiB2 demonstrates a remarkable enhancement in the electrochemical performance, exhibiting an excellent rate performance from 70 to 300 mA cm −2 . The energy efficiency is improved by 14.06% compared to the cell with the pristine electrode at 150 mA cm −2 for 300 cycles. This study is critical for not only proposing the promising electron‐deficient catalyst in VRFB application but also promoting fundamental understanding and offering a design strategy for achieving superior performance electrocatalysts in VRFB. Abstract : The fundamental issue of sluggish kinetics of V 2+ /V 3+ in vanadium redox flow battery is unraveled, demonstrating that the rate‐determining step of V 2+ /V 3+ is the electrochemical oxidation of V 2+ to V 3+ . Then the strategy of electron‐deficient sites is adopted as the electron collector accepting the unpaired electrons from V 2+ to accelerate the electrochemical conversion of V 2+ to V 3+ .